Transformasi Pembinaan Seni Pantomim di Sekolah Dasar : Peran SDN 1 Beureunuen sebagai Penggerak FLS3N di Kecamatan Mutiara Timur - Rasyidin Rasyidin; Muhammad Hamzah; Afifuddin Afifuddin (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Pantomime arts development in elementary schools plays a crucial role in fostering students' creativity, self-confidence, and expressive abilities. This study examines the transformation of pantomime development at SDN 1 Beureunuen, a school that hosts the National Student Arts Festival and Competition (FLS3N) in Mutiara Timur District, Pidie Regency. Using an active qualitative approach through participant observation, informal interviews, and documentation of participant development from 2019 to 2025, this study examines how creative pedagogy practices, constructivist approaches, and strengthening cultural identity are applied in the development process. The results show a significant increase in school participation in pantomime competitions, from only three groups in 2019 to twelve groups in 2025. SDN 1 Beureunuen's success in winning the gold medal at the national level in the FLS3N has been a driving factor in the paradigm shift of teachers, which in turn has encouraged the creation of a competitive arts ecosystem at the sub-district level. These findings confirm that the implementation of creative pedagogy and tiered development can improve the quality of arts learning and strengthen the capacity of teachers and students in areas with minimal resources.